Structural Characterization of [Zn(O2CAr4F‐Ph)2(TAD)] and Determination of Its Stable Conformation by DFT Calculations. (23rd May 2016) - Kim, Namseok; Baek, Il Hyun; Yoon, Sungho
Abstract : In the titled complex, [Zn(C19 H11 O2 F2 )2 (C8 H22 N4 )]∙0.5CH2 Cl2, the Zn 2+ cation, with two axial carboxylate ligands, is located in a hexacoordinate ZnO2 N4 environment. Two strong intra‐molecular hydrogen‐bonding interactions (CO⋯ H—N) between the carboxylate ligand and amine are observed, in addition to two weak intra‐molecular interactions among the aromatic C—H moieties and oxygen atoms of the carboxylate ligand. An inter‐molecular interaction is also detected between the aromatic C—H of the carboxylate ligand and the fluoro atom of the other carboxylate ligand. According to B3LYP/LANL2DZ calculations, the energy minimum of the title complex is achieved when the planes of the OCO moieties of the axial carboxylates are perpendicular, as observed in the crystal structure. Abstract :